QUALITY OF LIFE WITH BACK PAIN IN ACCORDANCE WITH LOCALIZATION (CERVICAL PAIN, BACK PAIN) - Khodjaeva , Zulfiya Amangeldievna; Madjidova , Yokuthon Nabievna (Innovative Development in Educational Activities, 2023)
This article is based on examination data of 486 patients, who were divided into two groups according to anatomical principles - patients with pain in the neck - cervical dorsalgia and in the lower back - lumbosacral dorsalgia. An analysis of the quality of life showed that according to the Vernon and Major test in patients with cervical dorsalgia, there was a significant decrease in the quality of life of patients and corresponded to moderate limitations in life activity (p < 0.05). Moreover, in patients with nociceptive pain the average scores were slightly higher, which corresponded to serious limitations in relation to patients with neuropathic pain. According to the Roland-Morris questionnaire, a decrease in the quality of life of patients with lumbosacral dorsalgia was established and corresponded to moderate limitations in life activity (p <0.05). The result of the Oswestry questionnaire states depression of vital functions with moderate and severe pain.